Chip formation and phase transformation in orthogonal machining of NiTi shape memory alloy: microstructure-based modelling and experimental validation. Issue 1 (2020) - Kaynak, Yusuf; Manchiraju, Sivom; Jawahir, I.S.; Biermann, Dirk
Abstract: Phase transformation and shape memory response of NiTi alloys are sensitive to the variation of temperature and stress. Thus, the phase transformation of NiTi alloys becomes more complex during machining process. This study presents findings from a major study involving modelling of machining-induced phase transformation of NiTi alloys performed by modifying Helmholtz free energy-based microstructure model. Orthogonal cutting tests were performed to validate the predicted outputs from the simulation, such as cutting forces, temperatures and chip morphology. This work provides a strong evidence that the developed new model can accurately predict the experimentally recorded outputs in machining of NiTi alloys.